MAGNETIC RESONANCE IMAGING IN SPORT MEDICINE - Dejanova Panev, Sandra; Vasilevska Nikodinovska, Violeta; Veljanovski, Dimitar; Prgova Veljanova, Biljana (University Ss. Cyril and Methodius in Skopje, 2022)
The use of appropriate imaging methods in sport medicine is very important in order to diagnose and evaluate the sport injuries. The aim of the study was to present the most frequent sport injuries, for the last 6 month period, using diagnostic modality as MRI, for better patient’s outcome. A number of 45 patients with sport injuries were diagnosed, regarding knee injury (n=28), shoulder injury (n=10), ankle injury (n=5) and hip injury (n=2). Out of all patients, 39 were male, and 6 were female. Regarding sport type, ball sports (n=40), bodybuilding (n=2), skiing (3) were included. In the study, the imaging device Magnetom Essenca 1.5T by Siemens, Erlangen, Germany was used. Most of the sport injuries were related to knee joint (62%), mostly involving the meniscus, common for ball sports, skiing, and gymnastics. The other injuries were related to the following body parts: shoulder joint (22%), ankle joint (11%) and hip (5%). MRI was found to be sensitive in diagnosis of soft tissue injuries, providing a good visualization in the musculoskeletal system, and may be clarified as a golden standard to diagnose and evaluate sport injuries.
Keywords: radiology; sport injuries; soft tissue